Customer Relation or Marketing In Business Management: Leveraging CRM for Competitive Advantage in Business Management (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Today’s businesses compete with multi-product offerings created anddelivered by networks, alliances and partnerships of many kinds. Both retainingcustomers and building relationships with other value-adding allies arecritical to corporate performance. The adoption of C.R.M. is being fuelled byrecognition that long-term relationships with customers are one of the mostimportant assets of an organization. The focus of CRM is on creating value forthe customer and the company over the longer term. When customers value thecustomer service that they receive from suppliers, they are less likely to lookto alternative suppliers for their needs .CRM enables organizations to gain‘competitive advantage’ over competitors that supply similar products orservices.